Glial cells as therapeutic targets for smoking cessation. (15th September 2020) - Kumar, Mohit; Adeluyi, Adewale; Anderson, Erin L.; Turner, Jill R.
Abstract: Smoking remains the leading cause of morbidity and mortality in the United States, with less than 5% of smokers attempting to quit succeeding. This low smoking cessation success rate is thought to be due to the long-term adaptations and alterations in synaptic plasticity that occur following chronic nicotine exposure and withdrawal. Glial cells have recently emerged as active players in the development of dependence phenotypes due to their roles in modulating neuronal functions and synaptic plasticity. Fundamental studies have demonstrated that microglia and astrocytes are crucial for synapse formation and elimination in the developing brain, likely contributing to why glial dysfunction is implicated in numerous neurological and psychiatric disorders. Recently, there is increasing evidence for the involvement of glial cells in drug dependence and its associated behavioral manifestations. This review summarizes the newly evaluated role of microglia and astrocytes as molecular drivers of nicotine dependence and withdrawal phenotypes. This article is part of the special issue on 'Contemporary Advances in Nicotine Neuropharmacology. Highlights: Tobacco use disorder accounts for 5 million premature deaths globally. Recent work suggests that glial cells in the CNS may contribute significantly to withdrawal symptomology. This review examines the therapeutic potential of targeting glial cells for treatment of nicotine withdrawal phenotypes.